A novel mouse running wheel that senses individual limb forces: biomechanical validation and in vivo testing - Roach, Grahm C. (J Appl Physiol (1985), 2012)
Biomechanical data provide fundamental information about changes in musculoskeletal function during development, adaptation, and disease. To facilitate the study of mouse locomotor biomechanics, we modified a standard mouse running wheel to include a force-sensitive rung capable of measuring the normal and tangential forces applied by individual paws. Force data were collected throughout the night using an automated threshold trigger algorithm that synchronized force data with wheel-angle data and a high-speed infrared video file. During the first night of wheel running, mice reached consistent running speeds within the first 40 force events, indicating a rapid habituation to wheel running, given that mice generated >2,000 force-event files/night. Average running speeds and peak normal and tangential forces were consistent throughout the first four nights of running, indicating that one night of running is sufficient to characterize the locomotor biomechanics of healthy mice. Twelve weeks of wheel running significantly increased spontaneous wheel-running speeds (16 vs. 37 m/min), lowered duty factors (ratio of foot-ground contact time to stride time; 0.71 vs. 0.58), and raised hindlimb peak normal forces (93 vs. 115% body wt) compared with inexperienced mice. Peak normal hindlimb-force magnitudes were the primary force component, which were nearly tenfold greater than peak tangential forces. Peak normal hindlimb forces exceed the vertical forces generated during overground running (50-60% body wt), suggesting that wheel running shifts weight support toward the hindlimbs. This force-instrumented running-wheel system provides a comprehensive, noninvasive screening method for monitoring gait biomechanics in mice during spontaneous locomotion.